Fatigue Life of Mooring Lines on External Turret Floating LNG for Different Pretension and Water Depth - Norman Mahdar Sabana; Eko Budi Djatmiko; Rudi Walujo Prastianto (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2019)
This paper studies fatigue life of mooring lines applied on turret-moored Floating LNG (Liquefied Natural Gas). Several case studies were designed to investigate the influence of mooring pretension and water depth on the fatigue life of mooring lines. Floating LNG with permanent external turret mooring system consists of 12 catenary lines arranged in 3 group with 4 lines each. Time domain simulation applied to calculated coupled dynamic response and mooring tension. Fatigue life is assessed using rainflow counting method, T-N curves and Palmgren-Miner rule. Analysis results for mooring pretension case show that case study 2 with lowest pretension (14%MBL) yields shortest mooring fatigue life of 1814.20 years compared to case study 1 (18%MBL) and 3 (22%MBL) with 2034.61 years and 2983.33 years respectively. Despite has the lowest dynamic line tension, case study 2 has larger tension range that results in the increased of fatigue damage. The increase in water depth will increase the mooring line length and its weight, so it results in the increase of fatigue damage. This is reflected in case study 5 (903m water depth), which has shortest mooring fatigue life of 1842.65 years compare to case study 1 (602m water depth) and 4 (301m water depth) with 2983.33 years and 3363.62 years respectively.